The Effect of Slow Deep Breathing on Reducing Pain Scale in Post-Operative Patients - Jannah, Uzlifatul; Sucipto, Ade; Laksono, Eko Budi (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Post-operative pain is the body's reaction to tissue damage caused by a surgical procedure so that the patient will experience discomfort, this can cause sleep quality problems, breathing problems, making the condition worse, the healing process and a long treatment period resulting in increased treatment costs. Pain management can be done using non-pharmacological therapy, one of which is slow deep breathing which will stimulate the parasympathetic nervous system thereby increasing endorphin production and reducing the pain level. The purpose of this research to determine whether there is an effect of slow deep breathing on reducing the pain scale in post-operative patients at Sultan Imanuddin Pangkalan Bun. The method in this research uses a quasi experimental with a one group pre-test and post-test design approach. Consecutive sampling technique, the sample in this study was 57 respondents who underwent 10 minute procedures on post-operative patients after 24 hours. This research instrument uses the NRS (Numeric Rating Scale), where the results of this research are analyzed using the Wilcoxon test. The results before slow deep breathing were carried out, almost all respondents experienced moderate pain, amounting to 45 respondents (78.9%). Meanwhile, after slow deep breathing were carried out by the majority of respondents experienced a change to mild pain, amounting to 34 respondents (59.6%). The results of statistical test analysis using the Wilcoxon test showed that the p value = 0.000, so the p value <  (0.05). There is an effect of slow deep breathing on reducing the pain scale in post-operative patients at Sultan Imanuddin Pangkalan Bun Regional Hospital.